Psychological Review of Visual Communication on the Instagram Platform: Analysis of Support for SDGs-5 Empowerment for Gender Equality - Aditia, Rafinita; Adhrianti, Lisa; Al-Nahari, Yusra Hamed (P3M Politeknik Negeri Media Kreatif, 2024)
This research conducts a comprehensive exploration of the psychological dimensions of visual communication on the Instagram platform, specifically analyzing its support for the Sustainable Development Goals (SDGs) with a focus on SDGs 5 for gender equality and empowerment. SDGs 5 is critical in promoting global gender equality and contributing to sustainable development. This research investigates the diverse roles of Instagram as a medium for disseminating information, education, advocacy, inspiration and collaboration regarding gender issues and women's rights. This research uses a qualitative approach using literature study methods to comprehensively investigate the psychological dimensions of visual communication on the Instagram platform, especially in support of SDGs 5 for empowering gender equality. These findings underscore Instagram's important contribution, revealing its effectiveness in shaping perceptions, attitudes and behavior regarding SDGs5 goal. Despite its positive impact, ethical considerations and challenges related to credibility, privacy and security require careful attention. This research provides valuable insights for stakeholders, offering a psychological review of visual communication on Instagram and improving strategies for achieving SDGs 5 empowerment and gender equality in a sustainable manner.